A meta-analytic review of food safety risk perception. (June 2020) - Machado Nardi, Vinicius Antonio; Teixeira, Rafael; Ladeira, Wagner Junior; de Oliveira Santini, Fernando
Abstract: Studies investigating food safety risk perception (FSRP) have substantially increased in recent years, particularly because of recent cases of food contamination. Most studies analysed the effects of FSRP antecedents and their consequences but reported heterogeneous effects. To consolidate these results and provide a more robust and parsimonious picture of FSRP, we conducted a meta-analysis of 128 empirical studies that investigated the key drivers and outcomes of FRSP and potential moderator variables. Our findings reveal the key drivers (trust, knowledge, subjective characteristics, and socio-demographic characteristics) of FSRP and a robust negative consequent effect on the willingness to buy (WTB). Also, we reveal the moderation role of the food origin, risk type, healthiness, shelf life and pleasure in the consequent effect. Our results contribute to the growing literature related to FSRP by consolidating previous results and help establish a foundation for further advancement in this topic. More importantly, our findings provide a more comprehensive picture of the FSRP phenomenon to help in the design of guidelines and rules that shape supplier behaviour to enhance food safety along the food supply chain. Highlights: Consolidation of previous empirical findings regarding the antecedents and consequent of food safety risk perception. Test of effect sizes for consumer behaviour antecedents of food safety risk perception. Test of effect size for the effect of food safety risk perception on consumer willingness to buy. Proposal and testing of moderators for the relationship between food safety risk perception and willingness to buy.